2012
DOI: 10.1039/c2dt30976a
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium amino carboxylate complexes as asymmetric hydrogen transfer catalysts

Abstract: The synthesis and characterization of optically active amino carboxylate complexes of formula [(η(6)-arene)Ru(Aa)Cl] (arene = C(6)H(6), C(6)Me(6), Aa = amino carboxylate) as well as those of the related trimers [{(η(6)-arene)Ru(Aa)}(3)][BF(4)](3) are reported. Trimerization takes place with chiral self-recognition: only diastereomers equally configured at the metal, R(Ru)R(Ru)R(Ru) or S(Ru)S(Ru)S(Ru), are detected. The crystal structures of the complexes [(η(6)-C(6)H(6))Ru(Pip)Cl] and [{(η(6)-C(6)Me(6))Ru(Pro)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 72 publications
1
17
1
Order By: Relevance
“…[22,23,[36][37][38][39][40] All complexes adopt the three-legged piano-stool (half-sandwich) configuration, as expected. As is the case with Cp ⁄ Ir amino acid complexes previously reported, the iridium atom becomes a pseudo-tetrahedral chiral center upon coordination of the amino acid, resulting in diastereomers that differ at configuration of the metal when using an enantiomerically pure amino acid.…”
Section: Synthesis Of Amino Acid Complexessupporting
confidence: 50%
See 3 more Smart Citations
“…[22,23,[36][37][38][39][40] All complexes adopt the three-legged piano-stool (half-sandwich) configuration, as expected. As is the case with Cp ⁄ Ir amino acid complexes previously reported, the iridium atom becomes a pseudo-tetrahedral chiral center upon coordination of the amino acid, resulting in diastereomers that differ at configuration of the metal when using an enantiomerically pure amino acid.…”
Section: Synthesis Of Amino Acid Complexessupporting
confidence: 50%
“…Prior work has shown that the ring based systems are the most selective, at least in the case of aromatic substrates [22,23,44,45]. This is due to only one active hydride complex being formed under ATH conditions.…”
Section: Asymmetric Transfer Hydrogenation Using Amino Acid Catalystsmentioning
confidence: 95%
See 2 more Smart Citations
“…10 The main difference concerns the Ir-Cl bond length in (R)-3b, which is slightly shorter than those observed in related α-amino carboxylates of the formula [(η 5 -C 5 Me 5 )Ir-(Aa)Cl] (range 2.409(3)-2.421(2) Å). 10c This dissimilarity may be related to minor differences in the intramolecular hydrogen bonding net established in the solid (see below), although a direct relationship is not easy to establish.…”
Section: Synthesis Of the Complexes [(η N -Ring)mcl(noh)][sbf 6 ]mentioning
confidence: 96%